# Singular

#### D.15.26.19 netPoly

Procedure from library `nets.lib` (see nets_lib).

Usage:
netPoly(P); P poly

Assume:
P is a poly

Return:
visual presentation of P over two rows

Theory:
A Singular object is converted into a character array (a Net) for on screen printing.

Example:
 ```LIB "nets.lib"; // from 3.3.1 Examples of ring declarations // ring R1 = 32003,(x,y,z),dp; poly q6=1; print(q6); ==> 1 netPoly(q6); ==> ==> 1 ==> poly q7=-1; print(q7); ==> -1 netPoly(q7); ==> ==> -1 ==> poly q8=2; print(q8); ==> 2 netPoly(q8); ==> ==> 2 ==> poly q9=-2; print(q9); ==> -2 netPoly(q9); ==> ==> -2 ==> poly q1=x+y+z; print(q1); ==> x+y+z netPoly(q1); ==> ==> x+y+z ==> poly q2=xy+xz+yz; print(q2); ==> xy+xz+yz netPoly(q2); ==> ==> xy+xz+yz ==> poly q3=2x3y3z4-3x4y5z6; print(q3); ==> -3x4y5z6+2x3y3z4 netPoly(q3); ==> 4 5 6 3 3 4 ==> -3x y z +2x y z ==> poly q4=x3y3z4-x4y5z6; print(q4); ==> -x4y5z6+x3y3z4 netPoly(q4); ==> 4 5 6 3 3 4 ==> -x y z +x y z ==> poly q5=-x3y3z4+x4y5z6; print(q5); ==> x4y5z6-x3y3z4 netPoly(q5); ==> 4 5 6 3 3 4 ==> x y z -x y z ==> ring R2 = 32003,(x(1..10)),dp; poly w6=1; print(w6); ==> 1 netPoly(w6); ==> ==> 1 ==> poly w7=-1; print(w7); ==> -1 netPoly(w7); ==> ==> -1 ==> poly w2=-x(1)-(2)-x(3); print(w2); ==> -x(1)-x(3)-2 netPoly(w2); ==> ==> -x(1)-x(3)-2 ==> poly w3=x(1)*x(2)+x(1)*x(2)+x(2)*x(3); print(w3); ==> 2*x(1)*x(2)+x(2)*x(3) netPoly(w3); ==> ==> 2x(1)x(2)+x(2)x(3) ==> poly w4=x(1)*x(2)-x(1)*x(2)-x(2)*x(3); print(w4); ==> -x(2)*x(3) netPoly(w4); ==> ==> -x(2)x(3) ==> poly w5=x(1)^2*x(2)^3*x(3)^4; print(w5); ==> x(1)^2*x(2)^3*x(3)^4 netPoly(w5); ==> 2 3 4 ==> x(1) x(2) x(3) ==> poly w8=x(1)+x(2)+x(3); print(w8); ==> x(1)+x(2)+x(3) netPoly(w8); ==> ==> x(1)+x(2)+x(3) ==> poly w9=x(1)+x(2)+x(3); print(w9); ==> x(1)+x(2)+x(3) netPoly(w9); ==> ==> x(1)+x(2)+x(3) ==> ring R3 = 32003,(x(1..5)(1..8)),dp; poly e1=x(1)(1)+x(2)(2)+x(3)(3); print(e1); ==> x(1)(1)+x(2)(2)+x(3)(3) netPoly(e1); ==> ==> x(1)(1)+x(2)(2)+x(3)(3) ==> poly e2=x(1)(1)*x(2)(2)*x(3)(3); print(e2); ==> x(1)(1)*x(2)(2)*x(3)(3) netPoly(e2); ==> ==> x(1)(1)x(2)(2)x(3)(3) ==> poly e3=x(1)(1)^2*x(2)(2)^3*x(3)(3)^4; print(e3); ==> x(1)(1)^2*x(2)(2)^3*x(3)(3)^4 netPoly(e3); ==> 2 3 4 ==> x(1)(1) x(2)(2) x(3)(3) ==> poly e4=-x(1)(1)^2*x(2)(2)^3*x(3)(3)^4-x(1)(1)^3*x(2)(2)^3*x(3)(3)^4; print(e4); ==> -x(1)(1)^3*x(2)(2)^3*x(3)(3)^4-x(1)(1)^2*x(2)(2)^3*x(3)(3)^4 netPoly(e4); ==> 3 3 4 2 3 4 ==> -x(1)(1) x(2)(2) x(3)(3) -x(1)(1) x(2)(2) x(3)(3) ==> ring r=32003,(x,y,z),lp; poly p=x4+4y4+4z4-x3-3y3-3z3+1x2+2y2+z2-x-1y-z1; p; ==> x4-x3+x2-x+4y4-3y3+2y2-y+4z4-3z3+z2-z netPoly(p); ==> 4 3 2 4 3 2 4 3 2 ==> x -x +x -x+4y -3y +2y -y+4z -3z +z -z ==> poly p2=x3yz+xy3z+xyz3-2x2yz-2xy2z-2xyz2+1xyz+x1yzxy1z; p2; ==> x3yz+x2y2z2-2x2yz+xy3z-2xy2z+xyz3-2xyz2+xyz netPoly(p2); ==> 3 2 2 2 2 3 2 3 2 ==> x yz+x y z -2x yz+xy z-2xy z+xyz -2xyz +xyz ==> poly p3=x+y+z-x2-3y-4z4+xy+xz+2xy-x2y-xz2-y2z2; p3; ==> -x2y-x2+3xy-xz2+xz+x-y2z2-2y-4z4+z netPoly(p3); ==> 2 2 2 2 2 4 ==> -x y-x +3xy-xz +xz+x-y z -2y-4z +z ==> ring r2=32003,(x(1..10)),lp; poly p=x(1)*x(2)*x(3)+2*x(1)^2+2*x(1)*x(2); p; ==> 2*x(1)^2+x(1)*x(2)*x(3)+2*x(1)*x(2) netPoly(p); ==> 2 ==> 2x(1) +x(1)x(2)x(3)+2x(1)x(2) ==> poly p2=x(1)^2*x(2)^3*x(3)^4-2*x(1)^1*x(2)^2+2*x(1)*x(2)*x(10); p2; ==> x(1)^2*x(2)^3*x(3)^4-2*x(1)*x(2)^2+2*x(1)*x(2)*x(10) netPoly(p2); ==> 2 3 4 2 ==> x(1) x(2) x(3) -2x(1)x(2) +2x(1)x(2)x(10) ==> ring r3=7,(x,y,z),lp; poly p=17x2+24y; p; ==> 3x2+3y netPoly(p); ==> 2 ==> 3x +3y ==> ring r4=(7,a,b,c),(x,y,z),Dp; poly p=2ax2+by-cz3; p; ==> (-c)*z3+(2a)*x2+(b)*y netPoly(p); ==> 3 2 ==> (-c)z +(2a)x +(b)y ==> ring r5=(7,a),(x,y,z),dp; minpoly = a^2+a+3; poly p=2ax2+y-az3; p; ==> (-a)*z3+(2a)*x2+y netPoly(p); ==> 3 2 ==> (-a)z +(2a)x +y ==> ring r6 = (complex,30,j),(x,y,z),dp; poly p=2x2+y-z3+20*j; p; ==> -z3+2*x2+y+(j*20) netPoly(p); ==> 3 2 ==> -z +2x +y+(j*20) ==> ```